POTENSI DAN PEMANFAATAN TANAMAN AREN (Arenga pinnata) DENGAN POLA AGROFORESTRI DI DESA PALAKKA KECAMATAN BARRU KABUPATEN BARRU - Syarifah Majnah Ruslan; Baharuddin Baharuddin; Ira Taskirawati (PERENNIAL, 2018)
Non-Timber Forest Products (HHBK) are part of the forest ecosystem that has a role to nature as well as to humans. One of the HHBKs that has high economic value and is one of the rural livelihoods of the community is Aren. This study aims to determine the potential and utilization of palm trees (aren) in Palakka Village Barru District Barru . The methods used are survey method and interview. Data analysis includes the potentials of sugar palms and description of the result of interview about the utilization of palm trees in Palakka village, Barru regency. The results showed that Palakka village has 15 palm trees that can already be in production, and 45 palm trees that have not been produced. Respondents utilize palm crop products as brown sugar and palm wine, other uses of palm trees that their fiber (ijuk) can be utilized to make palm-fiber broom; and the leaves are used as a funnel, roof of the house and palm-stick brooms. Key words: Potency, Utilization, Aren, Agroforestry